Exogenous silicon and salicylic acid applications improve tolerance to boron toxicity in field pea cultivars by intensifying antioxidant defence systems - Oliveira, Kevein; Pereira de Souza Junior, J.; Vantini Checchio, M.; Bennett, Sarita; de Cassia Alves, R.; Felisberto, G.; de Mello Prado, R.; Lupino Gratao, Pricilla (Elsevier, 2020)
Field peas (Pisum sativum L.) are widely cultivated throughout the world as a cool season grain and forage crop. Boron (B) toxicity is caused by high B concentration in the soil or irrigation water, and is particularly problematic in medium or heavier textured soil types with moderate alkalinity and low annual rainfall. Previous studies have indicated that B-toxicity increases oxidative stress in plants, and B-tolerance has been considered an important target in field pea plant breeding programmes. Inducers of tolerance may be a promising alternative for plant breeding. Little research has been conducted on the combined use of silicon (Si) and salicylic acid (SA) to remediate B-toxicity in field peas. The present study revealed the physiological and biochemical plant responses of applying Si + SA under B-toxicity (15 mg B L−1) on two Brazilian field pea cultivars (Iapar 83 and BRS Forrageira). A semi-hydroponic experiment was conducted using a completely randomized factorial design (2 × 5): with two field pea cultivars and five treatments which were formed by individual and combined applications of Si and SA under B-toxicity plus a control (control, B, B + Si, B + SA, and B + Si + SA). Si (2 mmol L−1) was applied to plants in two forms (root and leaf), while for SA (36 μmol L−1) only foliar applications were applied. Our results demonstrated that the combined use of exogenous Si + SA in field peas increased tolerance to B-toxicity through an intensified antioxidant plant defence system, resulting in a better regulation of reactive oxygen species (ROS) production and degradation. It significantly increased total chlorophyll and carotenoids contents, the activities of major antioxidant enzymes, and reduced MDA and H2O2 contents, resulting in increased fresh shoot and total plant dry biomass. The application of Si + SA alleviated the inhibitory effects of boron toxicity in field peas, resulting in greater plant growth by preventing oxidative membrane damage through an increased tolerance to B-excess within the plant tissue. Therefore, the use of Si + SA is an important and sustainable strategy to alleviate B-toxicity in field pea cultivation.